Misleading indicators [ how to reliably measure your business - Green, Philip , 1959-; Gabor, George (Praeger, 2012)
This book reveals the hidden and potentially misleading nature of measurements, empowering readers to avoid making critical business decisions that are harmful, unreasonable, unwarranted, or plain wrong.